A compact multi‐frequency GNSS scintillation model. Issue 4 (6th November 2018) - Rino, Charles; Breitsch, Brian; Morton, Yu; Jiao, Yu; Xu, Dongyang; Carrano, Charles
Abstract: We present a scintillation model that generates complex scintillation realizations using two‐dimensional phase‐screen calculations. A compact parameter set simplifies the model. The parameters can be adjusted to reproduce statistically equivalent realizations of target multi‐frequency GNSS intensity and phase scintillation time series or defaulted to representative values. Geometric range and TEC inputs can be incorporated to generate realizations of baseband GNSS signals for processor performance evaluation. Selecting model parameters is guided by an efficient encapsulation of the two‐dimensional phase‐screen theory. Motion of the propagation path through ionospheric structure generates temporal variation. The phase‐screen theory incorporates space‐to‐time conversion via a ratio of the Fresnel scale to an effective scan velocity. A universal strength parameter adjusts the strength of the scintillation. The model is an encapsulation of results that have been used for GPS performance analysis work that is cited in the paper. A MATLAB implementation of the model with examples has been made available.